(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
In this article the tourism resources of vegetation for the Shirak, Lori and Tavush Regions have been studied and evaluated. Three key areas were identified in which researches were carried out. As the main tourist resource for the region is the forest, the article presents an assessment of the forest for tourism activities. Based on the results of the work, a large-scale vegetation map of the study area was compiled.